Factorial structure of the California measure of mental motivation - Khiri, Adel; Behri, P. Nabil (The International tax journal, 2025)
The aim of the present research aims to examine the construct validity and reliability of the California measure of mental motivation in a culturally diverse distinct environment from the original environment. Mental motivation is a construct consisted 72 items distributed over 4 dimensional or factorial cognitions: mental focus, learning orientation, creative problem solving and cognitive integrity. Mental motivation data were collected from 631 Algerian university students (631) to investigate the multidimensional nature of the California mental motivation construct and the validity of the scale confirmatory factor analysis was conducted using AMOS. Results showed that mental motivation consisted 57 items over 4 factors, with a satisfactory fit between the data and the theoretical model and with acceptable reliability and sufficient validity.